Motivational Interviewing as an Intervention to Improve Antiretroviral Treatment Initiation Among People who Inject Drugs (PWID): A Pilot Study in Jakarta and Bandung, Indonesia - Sukmaningrum, Evi; Ayu, Astri P.; Wongso, Lydia Verina; Handayani, Miasari; Hendrianti, Sarahsita; Kawi, Nurhayati Hamim; Kusmayanti, Nur Aini; Sulaiman, Nurjannah; Irwanto; Law, Matthew; Wisaksana, Rudi (Current Drug Research Reviews, 2024)
Introduction: Progress towards the 95-95-95 target among People Who Inject Drugs (PWID) with Human Immunodeficiency Virus (HIV) infection was considerably low. A behavioral approach, such as motivational interviewing (MI), has been recognized as an effective strategy for improving HIV treatment outcomes among PWID. Objective: This study aimed at assessing the impact of MI counselling to improve ARV initiation among HIV-positive PWID. Methods: A cohort design pilot study was performed, and participants were recruited using a convenience sampling technique. Participants were PWID with HIV who accessed healthcare facilities in two Indonesian cities. Selected participants were assigned to an intervention group and a control group. The intervention group followed MI counselling, while the control group received ART following the standard of care. The participants were assigned to each group based on their preferences. The data was collected between January 2018 and January 2019. Results: In total, 115 PWID with HIV participated in this study in the intervention (n = 30) and control (n = 85) groups. All but one intervention group's participants started ART, while 68/85 in the control group did so. Receiving MI counselling significantly contributed to ART initiation. In addition, the participants were followed-up until 12 months after ARV initiation. During this period, we found that similar proportions of participants in both groups discontinued the treatment, and only a small number achieved HIV viral suppression. Conclusion: The positive effect of MI counselling on ART initiation provides insight into the possibility of its wider implementation. Further studies are needed to gain a deeper understanding of MI counselling and its effect on other outcomes of the HIV treatment cascade.
Keywords: healthcare